Amendment of soil by biochars and activated carbons to reduce chlordecone bioavailability in piglets. (November 2018) - Delannoy, M.; Yehya, S.; Techer, D.; Razafitianamaharavo, A.; Richard, A.; Caria, G.; Baroudi, M.; Montargès-Pelletier, E.; Rychen, G.; Feidt, C.
Abstract: Chlordecone (Kepone or CLD) is a highly persistent pesticide formerly used in French West Indies. Nowadays high levels of this pesticide are still found in soils which represent a subsequent source of contamination for outdoor-reared animals. In that context, sequestering matrices like biochars or activated carbons (ACs) are believed to efficiently decrease the bioavailability of such compounds when added to contaminated soils. The present study intends to test the respective efficiency of soil amendment strategies using commercial ACs or biochars (obtained by a 500 °C or 700 °C pyrolysis of 4 distinct type of wood). This study involved three experimental steps. The first one characterized specific surface areas of biochars and ACs. The second one assessed CLD-availability of contaminated artificial soils (50 μg g −1 of Dry Matter) amended with 5% of biochar or AC (mass basis). The third one assessed CLD bioavailability of those artificial soils through an in vivo assay. To limit ethically the number of animals, selections of the most promising media were performed between each experimental steps. Forty four castrated male 40-day-old piglets were exposed during 10 day by amended artificial soils according to their group (n = 4). Only treatment groups exposed through amended soil with AC presented a significant decrease of concentrations of CLD in liver and adipose tissue in comparison with the control group (p < 0.001). A non-significant decrease was obtained by amending artificial soil with biochars. This decrease was particularly high for a coconut shell activated carbon were relative bioavailability was found lower than 3.2% for both tissues. This study leads to conclude that AC introduced in CLD contaminated soil should strongly reduce CLD bioavailability. Highlights: CLD contaminated soil amendment by biochar or activated carbons (AC) was tested. Environmental availability of CLD was assessed using an in vitro ISO tests. Bioavailability of CLD was assessed in piglets. Amended soils with ACs limit CLD concentrations in liver and adipose tissue. Amended soils with biochars presented a limited reduction of bioavailability.